2017
DOI: 10.1088/1674-1056/26/10/104501
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of contact force in competitive evacuation

Abstract: Crowd force by the pushing or crushing of people has resulted in a number of accidents in recent decades. The aftermath investigations have shown that the physical interaction of a highly competitive crowd could produce dangerous pressure up to 4500 N/m, which leads to compressive asphyxia or even death. In this paper, a numerical model based on discrete element method (DEM) as referenced from granular flow was proposed to model the evacuation process of a group of highly competitive people, in which the movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Many experiments were conducted to collect parameters including velocity, location, density, evacuation time, and flow [47][48][49][50], but only a few were concentrated on the interactions between pedestrians while empirical data of the contact forces was scarce. In most of the current models, contact force models can be divided into two types: the customized model and the elastic force model [51][52][53]. However, their definitions are too simple to reflect the features of the interaction process.…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments were conducted to collect parameters including velocity, location, density, evacuation time, and flow [47][48][49][50], but only a few were concentrated on the interactions between pedestrians while empirical data of the contact forces was scarce. In most of the current models, contact force models can be divided into two types: the customized model and the elastic force model [51][52][53]. However, their definitions are too simple to reflect the features of the interaction process.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, when two or several pedestrians compete for the same position, there would be a collision between the pedestrians, increasing the risk of injury or crowd disturbances. In the previous work of Lin et al [ 38 ], it was found that the competitive behavior of pedestrians at the exit may cause force localization and compressive asphyxia of people. In the CA simulation, such behavior is associated with two or three pedestrians completing for one cell when updating their positions.…”
Section: Resultsmentioning
confidence: 99%
“…However, individuals involved in physical contacts may experience extremely high accelerations exceeding physiological limits due to simplified kinetic equations and idealized numerical calculations. This can be called "acceleration error during individual physical contacts", objectively requiring excessive contact forces as a guarantee 24 . During collisions, individuals are forced to experience high acceleration in order to avoid overlap and to quickly separate from others, and the contact force and penetration distance will be significantly abnormal if the acceleration is constrained by the physiological reality 25,26 .…”
Section: Modelling Physical Contacts To Evaluate the Individual Risk ...mentioning
confidence: 99%